Method for the Identification of Plant DNA in Food Using Alignment-Free Analysis of Sequencing Reads: A Case Study on Lupin - Raime, Kairi; Krjutškov, Kaarel; Remm, Maido (Frontiers in Plant Science, 2020)
Fast and reliable analytical methods for the identification of plants from degraded metagenomic samples play an important role in identifying the composition of complex mixtures of processed biological materials, including food, herbal products, gut contents or environmental samples. PCR and different barcoding methods commonly used for plant identification from metagenomic samples are often inapplicable due to DNA degradation, low amplification success or lack of detection power. We introduce the method that combines metagenomic sequencing and alignment-free k-mer based approach for the identification of plant DNA in processed metagenomic sample. Our method identifies plant DNA directly from metagenomic sequencing reads and does not need mapping or assembling the reads. We identified more than 31,000 Lupinus-specific 32-mers from assembled chloroplast genome sequences. We demonstrate that lupin DNA can be detected from controlled mixtures of sequences from target species (different Lupinus species) and closely related non-target species (Arachis hypogaea, Glycine max, Pisum sativum, Vicia faba, Phaseolus vulgaris, Lens culinaris, Cicer arietinum). We also demonstrate that these 32-mers are detectable from processed samples: lupin flour, conserved seeds and baked cookies containing different amount of lupin flour. In controlled conditions lupin specific components are detectable in baked cookies containing at minimum 0.05% of lupin flour in wheat flour.